A study of the effectiveness of current awareness service of Pusat Dokumentasi Ilmiah Nacional (PDIN) in meeting the information needs of its users - Rimbarawa, Kosam; Vallejo, Rosa M.; Buenrostro, Juan Jr. C. (Quezon City Institute of Library Science, University of the Philippines Diliman, 1983)
Discusses the effectiveness of the current awareness service of PDIN which is the Informasi Kilat (Information Bulletin) in meeting the information needs of its users. The basic research instrument was the questionnaire, surveying 250 users out of 500 registered subscribers with only 185 responded.
The author suggested the following changes in the current awareness service of PDIN: that the format and lay out of the Bulletin be improved; that a more aggressive marketing strategy be made; and, that PDIN review its subscription list and delete those not used.
Most of the CAS subscribers avail of the service to keep them abreast with developments in their fields. However, articles included in the bulletin oftentimes are not useful to them and not as current as it should be.
Mimeographed.
Special Problem (Master of Library Science)
Keywords: Current awareness services -- Indonesia; Information services -- Indonesia -- Use studies; Pusat Dokumentasi Ilmiah Nacional